Terephthalate and trimesate metal–organic frameworks of Mn, Co, and Ni: exploring photostability by spectroscopy. Issue 15 (1st March 2021) - Gupta, Nishesh Kumar; Bae, Jiyeol; Kim, Suho; Kim, Kwang Soo
Abstract : Photolytic cleaving of terephthalate and trimesate linkers of transition metal–organic frameworks. Abstract : We report a rapid synthesis for the fabrication of terephthalate and trimesate metal–organic frameworks (MOFs) of Mn, Co, and Ni by ultrasonication of organic linkers with freshly prepared metal hydroxides. The MOFs were characterized by various microscopic and spectroscopic techniques to understand their structural, functional, and optical properties. MOFs with low bandgap energy (1.88–2.73 eV) showed strong absorbance in the UV-visible range. MOFs were exposed to UV irradiation for 40 h to understand their photostability. The MOFs showed decreased surface area and porosity with CoBTC as an exception. PXRD was less convincing for exploring functional changes in the UV-irradiated MOFs. XPS predicted changes in the oxidation states of metal nodes, the degradation of the organic linkers, and decarboxylation process in many of the transition MOFs. The study predicted terephthalate-based MOFs as more photostable than corresponding trimesate-based MOFs. This study is one of the first attempts in exploring photostability of MOFs with Mn, Co, and Ni as nodes.